2021
DOI: 10.3390/cells10102760
|View full text |Cite
|
Sign up to set email alerts
|

NUAK Kinases: Brain–Ovary Axis

Abstract: Liver kinase B (LKB1) and adenosine monophosphate (AMP)-activated protein kinase (AMPK) are two major kinases that regulate cellular metabolism by acting as adenosine triphosphate (ATP) sensors. During starvation conditions, LKB1 and AMPK activate different downstream pathways to increase ATP production, while decreasing ATP consumption, which abrogates cellular proliferation and cell death. Initially, LKB1 was considered to be a tumor suppressor due to its loss of expression in various tumor types. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…NUAK1 lies on the short arm of chromosome 12, while NUAK 2 is on the short arm of chromosome 1. NUAK1 is expressed mainly in the brain, skin, and to a lesser extent in the breast, ovary, heart, and lung tissues; meanwhile, NUAK2 is found in the kidneys, ovary, breast, small bowel, and colon [ 27 ]. Molina et al reported that Cbioportal data showed genetic NUAK1 and NUAK2 alterations in ovarian and breast cancers.…”
Section: Proposed Shared Pathways For Disease Development In the Ovar...mentioning
confidence: 99%
“…NUAK1 lies on the short arm of chromosome 12, while NUAK 2 is on the short arm of chromosome 1. NUAK1 is expressed mainly in the brain, skin, and to a lesser extent in the breast, ovary, heart, and lung tissues; meanwhile, NUAK2 is found in the kidneys, ovary, breast, small bowel, and colon [ 27 ]. Molina et al reported that Cbioportal data showed genetic NUAK1 and NUAK2 alterations in ovarian and breast cancers.…”
Section: Proposed Shared Pathways For Disease Development In the Ovar...mentioning
confidence: 99%
“…Further investigation showed that SNHG3 significantly enhanced the proliferation, invasion, migration, and EMT of bladder cancer cells in vitro and in vivo through the regulation of GINS complex subunit 2 (GINS2), a member of the GINS complex involved in DNA replication, by “sponging” miR-515–5p [ 50 ]. Wang et al [ 51 ] showed that overexpression of SNHG6 promoted the EMT, migration, and invasion capabilities of bladder cancer cells by targeting tumor suppressive hsa-miR-125b, upregulating the expression of Snail1, Snail2, and NUAK family kinase 1 (NUAK1), which are key inducers of EMT and tumor metastasis [ 52 , 53 ]. Wang et al [ 54 ] found that upregulated SNHG7 expression in bladder cancer tissues and cells is positively correlated with poor prognosis in patients with bladder cancer.…”
Section: Lncrna-mediated Cerna Network In the Progression Of Bladder ...mentioning
confidence: 99%